2022
DOI: 10.1039/d2sc03479d
|View full text |Cite
|
Sign up to set email alerts
|

Total syntheses of naturally occurring antiviral indolosesquiterpene alkaloids, xiamycins C–F via Csp3–H functionalization

Abstract: Concise total syntheses of naturally occuring antiviral indolosesquiterpene alkaloids, xiamycin C (2a), D (2b), E (2c) and F (2d) have been achieved via a late-stage oxidative d-Csp3-H functionalization of an...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Only dimethyl-substituted indimicin B ( 26) was seen to have antitumor activity against the MCF-7 cell line with an IC 50 value of 10.0 µM. In order to characterize the function of gene spmH, which was predicted to be an L-Trp 5-halogenase, the authors inactivated this gene in strain SCSIO 03032 and obtained four bisindoles without a halogen substituent named spiroindimicins G-H (32)(33) and indimicins F-G (34-35) [29]. It was confirmed that spmH functioned as halogenase and acted in early biosynthesis using L-Trp as a substrate.…”
Section: Halogenated Bisindolesmentioning
confidence: 99%
See 1 more Smart Citation
“…Only dimethyl-substituted indimicin B ( 26) was seen to have antitumor activity against the MCF-7 cell line with an IC 50 value of 10.0 µM. In order to characterize the function of gene spmH, which was predicted to be an L-Trp 5-halogenase, the authors inactivated this gene in strain SCSIO 03032 and obtained four bisindoles without a halogen substituent named spiroindimicins G-H (32)(33) and indimicins F-G (34-35) [29]. It was confirmed that spmH functioned as halogenase and acted in early biosynthesis using L-Trp as a substrate.…”
Section: Halogenated Bisindolesmentioning
confidence: 99%
“…from B. gymnorrhiza in 2010 [32]. In recent years, compounds of this family have been found in marine Streptomyces, and have attracted attention because of their antibacterial, anti-human-immunodeficiency-virus (HIV) and anti-tumor activities [33]. Xiamycins C-E (40-42, Figure 5) were isolated from Streptomyces sp.…”
Section: Indole Sesquiterpenoidsmentioning
confidence: 99%
“…[68][69][70][71] Two structural revisions of bacterial MNPs were reported in 2022; the absolute congurations of the cyclic peptides ogipeptin A 237 and tumescenamide A 238 were corrected via total synthesis. 72,73 Other total syntheses of bacterial NPs included cyanogramides A and C, 74 (±)-nesteretal A, 75 lucentamycin A together with barmumycin, oxotomaymycin and oxoprothracarcin, 76 rakicidin F, 77,78 anthracimycin and anthracimycin B, 79 xiamycins C-F, 80 seongsanamide E, 81 salimabromide, 82 (+)-nocardioazine B, 83 the indolocarbazole alkaloid ZHD-0501, 84 (±)-spiroindimicins A, D, G and H, 85 bahamaolide A, 86 aqabamycin G, 87 and elmonin and pratenone A. 88 Reviews focused on marine bacterial NPs published during 2022 included publications on the biosynthesis of microbial terpenoids, 89 polyketides and non-ribosomal peptides, 90 ribosomal peptides, 91 and the anthracyclines.…”
Section: Introductionmentioning
confidence: 99%
“…Prior elegant approaches to monomeric indolosesquiterpene alkaloids have been independently developed by Baran (cyclization of a carbazole-anchored epoxy ether), 7 Krische (TiCl 4promoted Friedel-Cras cyclization), 9 Trotta (radical-induced polyene cyclization), 10 Li 11 (6p-electrocyclization/aromatization and indole C 2 -H bond activation/Heck annulation), Sarpong 12 (from (R)-carvone, using a photoinduced benzannulation sequence to forge the carbazole core), Dethe 13 (oxidative Heck/ aromatization for carbazole synthesis) and our group (following dCsp 3 -H activation of the pentacyclic skeleton of indolosesquiterpene alkaloid). 14 Herein, we report the total synthesis of both N-N atropodiastereomers of indolosesquiterpene alkaloids, namely dixiamycins A (1a) and B (1b), via a nature-inspired aerobic oxidation. Impressively, this work represents, to the best of our knowledge, the rst total synthesis of dixiamycin A (1a), clearly consistent with nature's oxidative approach to dixiamycins.…”
Section: Introductionmentioning
confidence: 99%
“…Prior elegant approaches to monomeric indolosesquiterpene alkaloids have been independently developed by Baran (cyclization of a carbazole-anchored epoxy ether), 7 Krische (TiCl 4 -promoted Friedel–Crafts cyclization), 9 Trotta (radical-induced polyene cyclization), 10 Li 11 (6π-electrocyclization/aromatization and indole C 2 –H bond activation/Heck annulation), Sarpong 12 (from ( R )-carvone, using a photoinduced benzannulation sequence to forge the carbazole core), Dethe 13 (oxidative Heck/aromatization for carbazole synthesis) and our group (following δCsp 3 –H activation of the pentacyclic skeleton of indolosesquiterpene alkaloid). 14 …”
Section: Introductionmentioning
confidence: 99%